The effects of cold water immersion on postexercise muscle soreness and fatigue - Lorete, C. J.; Fontaine, R. N.; Welsch, L. A.; Hoch, J. M. (International Journal of Athletic Therapy & Training, 2016)
Clinical Question: Is there evidence to suggest continuous cold water immersion (CWI) as a postexercise recovery intervention is more effective at reducing perceived muscle fatigue or soreness as measured using a Visual Analog Scale (VAS) when compared with passive rest in physically active adults?